Non‐invasive transcutaneous auricular vagus nerve stimulation prevents postoperative ileus and endotoxemia in mice. Issue 3 (8th November 2018) - Hong, Gun‐Soo; Zillekens, Anne; Schneiker, Bianca; Pantelis, Dimitrios; de Jonge, Wouter J.; Schaefer, Nico; Kalff, Joerg C.; Wehner, Sven
Abstract: Background: The cholinergic anti‐inflammatory pathway comprises the perception of peripheral inflammation by afferent sensory neurons and reflex activation of efferent vagus nerve activity to regulate inflammation. Activation of this pathway was shown to reduce the inflammatory response and improve outcome of postoperative ileus (POI) and sepsis in rodents. Herein, we tested if a non‐invasive auricular electrical transcutaneous vagus nerve stimulation (tVNS) affects inflammation in models of POI or endotoxemia. Methods: Mice underwent tVNS or sham stimulation before and after induction of either POI by intestinal manipulation (IM) or endotoxemia by lipopolysaccharide administration. Some animals underwent a preoperative right cervical vagotomy. Neuronal activation of the solitary tract nucleus (NTS) and the dorsal motor nucleus of the vagus nerve (DMV) were analyzed by immunohistological detection of c‐fos + cells. Gene and protein expression of IL‐6, MCP‐1, IL‐1β as well as leukocyte infiltration and gastrointestinal transit were analyzed at different time points after IM. IL‐6, TNFα, and IL‐1β serum levels were analyzed 3 hours after lipopolysaccharide administration. Results: tVNS activated the NTS and DMV and reduced intestinal cytokine expression, reduced leukocyte recruitment to the manipulated intestine segment, and improved gastrointestinal transit after IM. Endotoxemia‐induced IL‐6 and TNF‐α release was also reduced by tVNS. The protective effects of tVNS on POI and endotoxemia were abrogated by vagotomy. Conclusion: tVNS prevents intestinal and systemic inflammation. Activation of the DMV indicates an afferent to efferent central circuitry of the tVNS stimulation and the beneficial effects of tVNS depend on an intact vagus nerve. tVNS may become a non‐invasive approach for treatment of POI. Abstract : Activation of the cholinergic anti‐inflammatory pathway was shown to reduce the inflammatory response and improve outcome of postoperative ileus (POI) and sepsis in rodents. Herein, we tested if a non‐invasive auricular electrical transcutaneous vagus nerve stimulation (tVNS) affects inflammation in models of POI or endotoxemia.